2012
DOI: 10.1002/ijc.27885
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of p21 and p27 and hepatocellular cancer risk in a Chinese Han population: A case‐control study

Abstract: The p21 (Cip1/CDKN1A) and p27 (Kip1/CDKN1B) are members of the Cip/Kip family of cyclin-dependent kinase inhibitors, which can arrest cell proliferation and serve as tumour suppressors. We hypothesized that genetic variants in p21 and p27 may modify individual susceptibility to hepatocellular carcinoma (HCC). To test this hypothesis, we evaluated the associations of the polymorphisms of Ser31Arg and C120T in p21 and C-79T and Gly109Val in p27, as well as their combinations, with HCC risk in a case-control stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 52 publications
(111 reference statements)
1
14
0
Order By: Relevance
“…The G allele of the CDKN1B gene (rs2066827) has been associated with an increased risk for thyroid (13), squamous cell (28), prostate, and breast cancers (27,30). However, whether this polymorphism is associated with a better or worse prognosis remains uncertain (13,21,28,31). Pasqualini et al also found differences in the frequency of the WT (TT -53.6%) and polymorphic alleles Figure 1 Graphical representation of the relative contribution of the CDKN1B and CDKN2A genes to sporadic medullary thyroid carcinoma risk according to a stepwise regression analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The G allele of the CDKN1B gene (rs2066827) has been associated with an increased risk for thyroid (13), squamous cell (28), prostate, and breast cancers (27,30). However, whether this polymorphism is associated with a better or worse prognosis remains uncertain (13,21,28,31). Pasqualini et al also found differences in the frequency of the WT (TT -53.6%) and polymorphic alleles Figure 1 Graphical representation of the relative contribution of the CDKN1B and CDKN2A genes to sporadic medullary thyroid carcinoma risk according to a stepwise regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Nine polymorphisms were genotyped: CDKN1A (rs1801270 and rs1059234), CDKN1B (rs2066827 and rs34330), CDKN2A (rs11515), CDKN2B (rs2069426, rs3731239, and rs1063192), and CDKN2C (rs12885) using the TaqMan system (Applied Biosystems), as described previously (17). These SNPs were chosen because they have previously been associated with thyroid carcinoma or other tumor risks as described in Table 1 (13,15,16,20,21,22).…”
Section: Genotypingmentioning
confidence: 99%
“…Based on the search strategy, 1,641 records were retrieved. In this meta-analysis, ten studies15161718192021222324 involving 11,214 cases and more than 8,776 controls were identified from the electronic databases according to the inclusion criteria. Characteristics of the identified studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size in these studies ranged from 143 to 9,030 individuals. The genotype distributions of cases and controls were presented in seven studies15161718202324. Other three studies192122 only reported the ORs with 95% CIs in more than two of genetic models, such as homozygous model, heterozygous model, recessive model, or allele model; of these three studies, one study19 reported ORs and 95% CIs in two different populations, which was treated as two distinct reports in the combined analysis.…”
Section: Resultsmentioning
confidence: 99%
“…p21 and p27 are famous cyclin-dependent kinase inhibitors. They are members in the Cip/Kip family, which can arrest the cell cycle and serve as tumor suppressors (21). Cell cycle arrest contributes to proliferation inhibition and apoptosis induction.…”
Section: Discussionmentioning
confidence: 99%